Sub-chronic oral toxicity study of Kushta Hajrul-Yahood (A Herbo-mineral Unani formulation) in Wistar rats - Showkat A. Dar, Seema Akbar, Khalid Ghazanfar, Mariya Hamdani, Tazeen Nazir, Masood S Mir, Akbar Masood, Humma Rafiq, Showkat A Ganie (Journal of Applied Pharmaceutical Science, 2016)
PD (Kushta Hajrul Yahood) is a Unani drug used for the treatment of renal and bladder calculi. The aim of the study was to demonstrate the scientific validity of detoxification method for preparation of Kushta and also to investigate the sub-chronic oral toxicity study of PD and CM (Crude material of Kushta Hajrul Yahood-its Un-detoxified form) in Wistar rats. Animals were orally treated once daily with test substance at the dose level of 1000mg and its two sub fractions 500 and 250mg/kg body weight for 90-days. Rats were observed throughout the study period. Body weight, feed and water consumption were recorded weekly. Overnight fasted rats were sacrificed on 91st day. Blood sample were collected for Haematological and biochemical studies. Organs were collected to record the organ weight and tissues for histology. The results showed elevation of liver enzymes due to the administration of PD at the dose level of 1000mg/kg body weight only, while-as in case of CM, there were significant elevation of liver enzymes at all the three doses. This elevation of enzymes also correlates with histopathological changes in liver tissues. This study concludes that the method of detoxification adopted for preparing Kushta substantially reduces the elements of toxicity.
Keywords: Sub-chronic toxicity, Hajrul-Yahood, biochemical parameters, haematological parameters, Histopathology.